REALIZATION OF THE LAWS OF DYNAMIC SYMMETRY IN THE DESIGN OF THE ENVIRONMENT BY MEANS OF COMPUTER THREE-DIMENSIONAL MODELING - Vyshnevska, О. V.; Bodnar , O. Y. (Art and Design, 2023)
The purpose of the study is to determine the possibilities of applying the laws of dynamic symmetry in the design of the environment through computer three-dimensional modeling. Methodology. The study used methods of historical and logical analysis of the problem of the role of dynamic symmetry in nature, art, and design; methods of comparison, comparison, and generalization. According to the transdisciplinary approach, dynamic symmetry is considered as a phenomenon of nature, a concept of geometry, and a principle of forming in design. Results. The concepts of "dynamic symmetry" and "phyllotaxis" in the research of D. Hambidge have been analyzed, and the peculiarities of using the above categories to analyze the proportions of art and design objects have been revealed. It has been established that modern methods of computer modeling make it possible to use the laws of dynamic symmetry in environmental design. On the examples of design developments of interior elements (lighting fixtures, spiral staircases), the methods of combining the patterns of change in the shape and size of model elements, orientation in space, and on the plane have been shown. The scientific novelty of the research is in the implementation of approaches to the laws of dynamic symmetry in the design of the environment through computer three-dimensional modeling. Practical significance. The results of the study can be used in the study of the disciplines "3D modeling in environmental design", "Fundamentals of computer design", "Environmental design", "Design of furniture and equipment".